Substrates Preference for Pupation on Sawfly Notofenusa surosa (Hymenoptera: Tenthredinidae) - Pietrantuono, Ana Laura (2015)
The choices made by insects at different stages of their life cycle are critical for the individual and progeny success. In the case of leaf-miners, during larval development they are not able to make choices until the emergence from the leaf, after which the larva falls to the ground and begins pupation. According to needs, preferences and soil properties, the larva could achieve a suitable substrate for the development of the pupa. Our aim was to study the preferences for pupation substrates of Notofenusa surosa larvae, leaf-miners of Nothofagus obliqua, in relation to soil properties. We selected different types of substrates (including volcanic ash) and conducted paired preference tests. The substrate was considered chosen when the larva selected it and formed the pupa (response variable). According to data obtained, several models were performed to determine the probability of individuals to choose a particular option depending on its preferences and substrates’ properties. These larvae are able to discriminate the different options offered and choose their pupation substrate according to the percentage of organic matter.